The Dragon Fruit Business Development Strategy using Analytical Hierarchy Process - Filsa Rezky Amaliah; Rosmawaty Rosmawaty; Wa Ode Yusria (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2023)
This study aims to analyze the priority strategy for developing dragon fruit farming using the Analytical Hierarchy Process. This research was conducted from October to November 2021 in Lalonggida, Watulondo Village, Puuwatu District, Kendari City. The data consists of primary and secondary data collected through in-depth interviews and questionnaires. Key informants are resource persons consisting of policymakers (Secretary of the Puuwatu Sub-district and Lalonggida Village Head), agricultural extension officers, administrators, and members of the Matirodeceng farmer group. Data analysis used AHP ( Analytical Hierarchy Process) analysis. The results of this study indicate that the priority of the Matirodeceng farmer group's primary strategy is to develop dragon fruit farming through collaboration and institutional strengthening, providing business capital and agricultural machinery.